Social innovation: Definitions and models reconsidered - Attila Havas; György Molnár (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
Social innovation (SI) has become a widely used buzzword in recent years. It is portrayed as a solution - almost a panacea - to many different types of societal and environmental problems. We can also perceive this development as a strong impetus to clarify its meaning, the actors involved in SI processes, their objectives, activities and interactions, as well as SI processes. Hence, this paper critically reconsiders the plethora of SI definitions, as well as recent SI models. As our main results, we propose a new, nominal definition and then develop a new model of SI, inspired by the multi-channel interactive learning model of business innovations. The new definition and model can offer a pertinent conceptual framework for SI policy-makers, policy analysts, as well as practitioners when devising, implementing or assessing SI.
Keywords: O30; O35; O38; 330; Definitions and models of social innovation; Multi-channel interactive learning